Implementing self-management: a mixed methods study of women's experiences of a postpartum hypertension intervention (SNAP-HT) - Cairns, AE; Tucker, KL; Crawford, C; McManus, RJ; Powell, J (BioMed Central, 2020)
Background Self-management strategies are effective in a number of medical conditions; however, implementation studies have demonstrated adoption into clinical practice can be problematic. The process of implementation was explored during a pilot randomised controlled trial evaluating postpartum blood pressure self-management in women with medicated hypertensive disorders of pregnancy. Methods A mixed methods study using semi-structured interviews with a qualitative and a scored (quantitative) component were undertaken as part of a pilot randomised controlled trial (SNAP-HT) in postnatal women with medicated gestational hypertension or pre-eclampsia. Women were randomised to usual care or blood pressure self-management. Self-management entailed daily home blood pressure monitoring and automated medication reduction via telemonitoring. Women from both groups optionally consented to participate in audio-recorded interviews at 4 weeks and 6 months postpartum. Interview questions were developed to explore the proposed benefits of self-management and the constructs of normalisation process theory. Participants provided a score (Likert scale 1–5) for each question and were encouraged to expand upon these answers through further discussion. The interviews were transcribed and analysed using the framework approach. Results Sixty-eight women, 34 from each randomised group, completed at least one audio-recorded interview. Several overarching themes emerged from analysis of 126 interview transcripts: control; convenience; confidence, communication and knowledge; concern; constraints; and components of the intervention. In the scored component of the analysis, both groups reported feeling more in control of their condition postpartum compared to during pregnancy, more so in those self-managing at both 4 weeks and 6 months: adjusted differences 0.6 (95% confidence interval [CI] 0.2 to 1.1) and 0.7 (95% CI 0.3 to 1.2) respectively. Conclusions Interviews and quantitative data showed that self-management enhanced women’s sense of control and improved their blood pressure-related anxiety. Prior to taking part, a few women anticipated that home monitoring might increase anxiety, but stated that it had the opposite effect. Self-management was perceived as more flexible and reactive and as enabling more targeted down-titration of medication. These data provide considerable support for blood pressure self-management postpartum and reinforce the effectiveness of the intervention used in this study. Trial registration ClinicalTrials.gov: NCT02333240. Prospectively registered on 7 January 2015.